Crystallographic analysis of FAD‐dependent glucose dehydrogenase. Issue 8 (1st August 2015) - Komori, Hirofumi; Inaka, Koji; Furubayashi, Naoki; Honda, Michinari; Higuchi, Yoshiki
<x xml:space="preserve">Abstract</x> An FAD‐dependent glucose dehydrogenase (GDH) from Aspergillus terreus was purified and crystallized at 293 K using the sitting‐drop vapour‐diffusion method. A data set was collected to a resolution of 1.6 Å from a single crystal at 100 K using a rotating‐anode X‐ray source. The crystal belonged to space group P21, with unit‐cell parameters a = 56.56, b = 135.74, c = 74.13 Å, β = 90.37°. The asymmetric unit contained two molecules of GDH. The Matthews coefficient was calculated to be 2.2 Å3 Da−1 and the solvent content was estimated to be 44%.